Brazilian legislation and virtual crimes in the state of Tocantins between 2021 and 2023 - Macedo, Eva Barros dos Santos; Oliveira Filho, Enio Walcácer de (JRG Journal of Academic Studies, 2024)
The present study presents an analysis of the registration numbers of cybercrimes occurring in Tocantins between the years 2021 and 2023. It presents a legislative outline of laws that cover crimes of a virtual nature, as well as their spheres of action. In addition to promoting reflection in terms of understanding the difficulties of legislation in cybercrimes. To this end, the inductive method was adopted, including exploratory research based on data and bibliographical and legislative reviews that made it possible to conclude that legislative ineffectiveness combined with the difficulties experienced by professionals as the main cause of punitive inefficiency.